2022
DOI: 10.1101/2022.06.20.496791
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bilateral JNK activation is a hallmark of interface contractility and promotes elimination of aberrant cells

Abstract: Tissue-intrinsic defence mechanisms eliminate aberrant cells from epithelia and thereby maintain the health of developing tissues or adult organisms. 'Interface contractility' comprises one such distinct mechanism that specifically guards against aberrant cells, which undergo inappropriate cell fate and differentiation programs. The cellular mechanisms which facilitate detection and elimination of these aberrant cells are currently unknown. We find that in Drosophila imaginal discs, interface contractility is … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 82 publications
0
1
0
Order By: Relevance
“…The pathway is tightly controlled to regulate proliferation, but also vein cell fate patterning in late larval and pupal wing tissue 49 . We previously reported that Ras V12 -expressing cells elicit interface surveillance in imaginal discs, as evident by enrichment of Actin at clone boundaries, clone smoothening and activation of JNK interface signaling (Fig 7A) 3,50 . Yet, Ras V12 -expressing cells evade elimination by apoptosis because of the potent anti-apoptotic properties conferred by Ras V12expression, thereby allowing these cells to remain in the tissue and form slow-growing tumors 4 .…”
Section: Oncogenic Ras But Not Classical Cell-cell Competition Alters...mentioning
confidence: 83%
“…The pathway is tightly controlled to regulate proliferation, but also vein cell fate patterning in late larval and pupal wing tissue 49 . We previously reported that Ras V12 -expressing cells elicit interface surveillance in imaginal discs, as evident by enrichment of Actin at clone boundaries, clone smoothening and activation of JNK interface signaling (Fig 7A) 3,50 . Yet, Ras V12 -expressing cells evade elimination by apoptosis because of the potent anti-apoptotic properties conferred by Ras V12expression, thereby allowing these cells to remain in the tissue and form slow-growing tumors 4 .…”
Section: Oncogenic Ras But Not Classical Cell-cell Competition Alters...mentioning
confidence: 83%